Analisis Pengaruh Kinerja Keuangan Terhadap Kemampuan Membayar Zakat - Harahap, Ima Khoirunnisa; Harahap, Darwis; Zein, Aliman Syahuri (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2020)
Abstract Zakat is one of the social activities carried out by PT. Bank Syariah Mandiri and that must be paid when it reaches the nisab. The calculation of zakat funds issued is 2.5% of profit before tax. To determine the ability of banks to generate relative profits using the Ratio of Return on Assets (ROA) and Return on Equity (ROE). Based on data obtained from PT. Bank Syariah Mandiri percentage of ROA, ROE and Zakat fluctuated in 2008-2016, however, the increase in percentage that occurred in ROA and ROE was not always followed by an increase in zakat. This research was conducted to determine whether ROA and ROE affect the ability to pay zakat in PT. Bank Syariah Mandiri, either partially or simultaneously. This research data is a quantitative research. And the data analysis technique used multiple linear regression method using the SPSS version 22.00 computer program. The results of the research partially (t test) state that ROA has no effect on zakat. Meanwhile, ROE affects zakat. ROA and ROE influence on zakat. Keywords: ROA, ROE, Zakat